Roeping en opleiding in 'n spesifieke konteks: vyf trinitariese stellinge oor motivering en oriëntasie - R. Venter (Acta Theologica)
The article endeavours to discuss, from a theological point of view, continuing theological education, and proposes that a consistently trinitarian approach will address crucial aspects relating to further education for ministers. The argument is developed in the form of five statements. It is argued that a trinitarian perspective responds to the need for a focus on theological education and motivates the practice of continuous training. A study of the contemporary context is required by trinitarian faith which also informs matters of basic orientation and content.